Heterogenization of Schiff base complexes on mesoporous silica and their application as catalysts in the oxidative transformation of alcohols - Joubert, Corli (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.